2002
DOI: 10.1002/app.11000
|View full text |Cite
|
Sign up to set email alerts
|

Influence of particle surface properties on film formation from precipitated calcium carbonate/latex blends

Abstract: ABSTRACT:The surface properties of films prepared from a blend of precipitated calcium carbonate pigment (PCC) and poly(n-butyl methacrylate-co-n-butyl acrylate) [P(BMA/BA); T g ϭ 0°C] latex were investigated in terms of the surface characteristics of the PCC and P(BMA/BA) latex particles. It was found that the presence of carboxyl groups on the P(BMA/BA) latex particles significantly improved the uniformity of the distribution of the PCC particles within the P(BMA/BA) copolymer matrix and the gloss of the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 9 publications
0
11
1
Order By: Relevance
“…The contact resistance between the conductive fillers is increased by the encapsulation of these fillers with a layer of insulating polymer [73]. It is reasonable that the ITO and ATO nanoparticles interact differently with the insulating matrix polymer during coating formation [20] because they may have different surface chemistry [38][39][40][41][42][43]60,61], leading to a different polymer distribution among the ATO and ITO nanoparticles. Such a difference distribution may also influence the percolation threshold.…”
Section: Electrical Conductivitymentioning
confidence: 98%
See 1 more Smart Citation
“…The contact resistance between the conductive fillers is increased by the encapsulation of these fillers with a layer of insulating polymer [73]. It is reasonable that the ITO and ATO nanoparticles interact differently with the insulating matrix polymer during coating formation [20] because they may have different surface chemistry [38][39][40][41][42][43]60,61], leading to a different polymer distribution among the ATO and ITO nanoparticles. Such a difference distribution may also influence the percolation threshold.…”
Section: Electrical Conductivitymentioning
confidence: 98%
“…Examples include architectural [1,2], paper [3,4], biological [5][6][7], and electrical and optical coatings [8][9][10][11], as well as other industrial paints and coatings [12][13][14][15][16][17][18][19][20]. These water-borne systems are environmentally friendly and easily processed.…”
Section: Introductionmentioning
confidence: 98%
“…Various kind of small particles, such as carbon blacks, but also clays [17][18][19], calcium carbonates [20], silicon dioxide [21][22][23][24][25] and magnesium hydroxide, etc. have already been used to reinforce latex in the past 50 years.…”
Section: Introductionmentioning
confidence: 99%
“…Systematic study of the techniques have been found in the literature: (a) to apply two-step milling process for producing rubber/filler composite; (b) to introduce the dispersants or coupling agents [11][12][13]; (c) to pre-treat carbon surface or chemically modify elastomer chains, in order to enhance the physical and chemical interaction at the interface of polymer-filler [14][15][16]; (d) to disperse CBs into rubber latex or solution instead of solid mixing [17][18][19][20][21][22][23][24][25]. No significant improvement was observed in the reinforcing activity of carbon black treated by (a), (b) and (c).…”
Section: Introductionmentioning
confidence: 99%
“…Coagulating rubber latex and aqueous dispersion of clay is proven to be a simple technique for obtaining films of high strength and tear resistance [10][11][12][13][14][15][16]. Calcium carbonate particles have also been used to improve the mechanical performance of latex products [17][18][19]. On the other hand, carbon black has received less attention as reinforcing filler [20], opposed to silica grades [21][22][23][24][25], due to its hydrophobicity.…”
Section: Introductionmentioning
confidence: 99%